Household`s Disagreement on Inflation Expectations and Socioeconomic Media Exposure in Germany - Jan-Oliver Menz; Philipp Poppitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Inflation expectations are often found to depend on socioeconomic and demographic characteristics of households, such as age, income and education, however, the reasons for this systematic heterogeneity are not yet fully understood. Since accounting for these expectation differentials could help improve the communication strategies of central banks, we test the impact of three sources of the demographic effect on inflation expectations using data for Germany. Overall, our findings suggest that household-specific inflation rates and group-specific news consumption accounts for the higher forecast errors of younger and older households, households with lower income and unemployed survey respondents, while households inflation perceptions only play a minor role.
Keywords: C53; D84; E37; 330